2017
DOI: 10.3945/jn.116.243907
|View full text |Cite
|
Sign up to set email alerts
|

Social Franchising and a Nationwide Mass Media Campaign Increased the Prevalence of Adequate Complementary Feeding in Vietnam: A Cluster-Randomized Program Evaluation

Abstract: Background: Rigorous evaluations of health system–based interventions in large-scale programs to improve complementary feeding (CF) practices are limited. Alive & Thrive applied principles of social franchising within the government health system in Vietnam to improve the quality of interpersonal counseling (IPC) for infant and young child feeding combined with a national mass media (MM) campaign and community mobilization (CM).Objective: We evaluated the impact of enhanced IPC + MM + CM (intensive) compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
(45 reference statements)
3
29
0
Order By: Relevance
“…In Bangladesh, combined intensive interventions resulted in significant improvements in exclusive breastfeeding (EBF) (by 36.2 percentage points—pp), early initiation of breastfeeding (EIBF) (by 16.7 pp) ( 16 ), and CF practices (16.3 pp, 14.7 pp, 22 pp, and 24.6 pp for minimum dietary diversity, minimum meal frequency, minimum acceptable diet, and consumption of iron-rich foods, respectively) ( 16 , 17 ). Similar results were obtained in Vietnam ( 18 ); and patterns of increased EBF, EIBF, and multiple CF practices in intervention areas were observed in Ethiopia ( 15 ). Evaluations of other large-scale BCC interventions similarly showed a significant increase in EBF through BF counseling within a routine health service delivered by community health agents in Brazil ( 19 ) and improvements in both BF and CF practices through peer counseling by mother support groups in India ( 20 ).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In Bangladesh, combined intensive interventions resulted in significant improvements in exclusive breastfeeding (EBF) (by 36.2 percentage points—pp), early initiation of breastfeeding (EIBF) (by 16.7 pp) ( 16 ), and CF practices (16.3 pp, 14.7 pp, 22 pp, and 24.6 pp for minimum dietary diversity, minimum meal frequency, minimum acceptable diet, and consumption of iron-rich foods, respectively) ( 16 , 17 ). Similar results were obtained in Vietnam ( 18 ); and patterns of increased EBF, EIBF, and multiple CF practices in intervention areas were observed in Ethiopia ( 15 ). Evaluations of other large-scale BCC interventions similarly showed a significant increase in EBF through BF counseling within a routine health service delivered by community health agents in Brazil ( 19 ) and improvements in both BF and CF practices through peer counseling by mother support groups in India ( 20 ).…”
Section: Introductionsupporting
confidence: 80%
“…Recent impact evaluations of large-scale behavior-change communication (BCC) interventions to improve IYCF practices in several countries have shown that intensive interpersonal counseling (IPC) combined with mass media (MM) and community mobilization (CM) activities have positive impacts on breastfeeding (BF) ( 15 , 16 ) and complementary feeding (CF) practices ( 15 , 17 , 18 ). In Bangladesh, combined intensive interventions resulted in significant improvements in exclusive breastfeeding (EBF) (by 36.2 percentage points—pp), early initiation of breastfeeding (EIBF) (by 16.7 pp) ( 16 ), and CF practices (16.3 pp, 14.7 pp, 22 pp, and 24.6 pp for minimum dietary diversity, minimum meal frequency, minimum acceptable diet, and consumption of iron-rich foods, respectively) ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, Concentra on among the poor was greatest and was sta s cal significant for child underweight and stun ng (Limwa ananon S, Tangcharoensathien V, Prakongsai P, 2010). The general improvements in socioeconomic status observed during the study period in Vietnam led to significant improvements in anthropometric indicators over me (Rawat R, Nguyen PH, Tran LM, Hajeebhoy N, Nguyen H Van, Baker J, et al, 2017). In Cambodia, stun ng had weak correla on with household's wealth index (r = 0.06, P = 0.088) (Reinbo A, Kuchenbecker J, Herrmann J, Jordan I, Muehlhoff E, Kevanna O, et al,2015) and in other study, child stun ng showed a sta s cally significant associa on with household wealth index scores (Ikeda N, Irie Y, Shibuya K, 2013).…”
Section: Ses (Socio-economic Status)mentioning
confidence: 66%
“…Introduc on of CFs earlier than 4 months of age was a risk factor for being underweight (age-adjusted odds ra o (OR adjust-age) = 1.7, 95% confidence interval (CI) = 1.2-2.5) and for stun ng (OR adjust-age = 1.6, 95% CI = 1.1-2.3) (Zhao A, Gao H, Li B, Zhang J, Win NN, Wang P, et al ,2016). But in Vietnam, although Social Franchising significantly improving Complementary Feeding Prac ce but it was not improved child growth (Rawat R, Nguyen PH, Tran LM, Hajeebhoy N, Nguyen H Van, Baker J, et al, 2017). In Cambodia, None of the WHO IYCF indicators was associated with LAZ, whereas CFI showed significant associa on with LAZ (P = 0.01).…”
Section: Kesehatan Komunitas J U R N a L J Infant And Young Child Feementioning
confidence: 98%
See 1 more Smart Citation